The Impact Of Revenue Diversification On Bank Profitability And Stability: Evidence From Indonesia Banking Industry - Febby Olvyana Susanto; Noval Adib; Arum Prastiwi (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose: This study aims to examine the effect of income diversification on the financial health of banks in Indonesia, focusing on income sources that significantly contribute to improving profitability and financial stability. Methodology/approach: This study uses a quantitative approach (positivism) which an associative nature. The research population consists of banking companies listed on the IDX from 2020-2023, with a sample of 168 observations selected using the purposive sampling method. The data analysis technique employs panel data regression using Eviews 12 software. Findings: The results of the regression analysis show that, total revenue diversification has a positive effect on profitability, but a negative effect on financial stability. Meanwhile, the proportion of non-interest income has a negative effect on profitability, but a positive effect on financial stability, with commission income as the most stable component of non-interest income and increasing profitability. Practical implications: This research contributes to helping bank management to be prudent in implementing income diversification strategies, by prioritizing interest income and avoiding high risk in non-interest income. The findings can also be taken into consideration for regulators in encouraging a balanced diversification strategy to maintain financial stability. Originality/value: The update in this study uses additional measurements to reveal the value of diversification that has not been discussed by previous researchers. This measurement is to differentiate diversification conditions that have similar values so that they are not considered the same. In addition, researchers also added control variables to increase the validity of the research